Esporte e lazer para o desenvolvimento rural sustentável: contribuições para a sucessão na agricultura familiar - Melo, Eder Tiago (2023)
Rural succession is a much-discussed topic these days. One can see the difficulty for it to occur, due to numerous situations: masculinity in the field, difficulty in the view of parents in providing continuity for their children, view of parents in relation to suffering life in the countryside, little opportunity for studies, amounts paid for organic products in relation to family support. On the other hand, we see few studies relating the succession in relation to sport and leisure, and the capacity that they have in relation to the feeling of belonging in a locality. Through field research, quantitative/qualitative, we sought information from youth leaders in the districts with the highest population in Marechal Cândido Rondon, questioning about the conditions of the physical structure, maintenance and public policies related to sport and leisure in the rural area of this municipality. The survey also gathered information about the young people’s view of how much sport and leisure can be a helper for the maintenance of these young people in the rural environment. The results were significant, demonstrating that the leadership sees this as an alternative that can reap beneficial results so that the feeling of being part of a community occurs and that sport and leisure can contribute to permanence. Former youth leaders and pioneers of associations and clubs in these districts were also interviewed to talk about how it worked and how they perceive the interaction of young people in the communities.